Classroom-Situated Willingness to Communicate: Student Teachers of EFL in Spain - José Luis Estrada-Chichón; Francisco Zayas-Martínez; Roberto Sánchez-Cabrero (MDPI AG, 2023)
This exploratory mixed-methods research involves an intra-/intergroup replication design to analyse the classroom-situated willingness to communicate (WTC) in English foreign language (EFL) student teachers of early childhood education according to grouping, group member familiarity, and EFL proficiency. The novelty lies in the adaptation from face-to-face to virtual teaching while student teachers attended a didactics course at the University of Cádiz (Spain). Results show that there are no significant differences in WTC concerning teaching modality except for grouping. Conclusions imply that classroom-situated WTC is not affected by teaching modality when instruction aims at language acquisition by fostering oral communicative interaction.